2021
DOI: 10.3389/fspas.2021.723530
|View full text |Cite
|
Sign up to set email alerts
|

Further Astrochemical Insights From Bond Strengths of Small Molecules Containing Atoms From the First Three Rows of the Periodic Table

Abstract: The atoms contributing to the strongest “single bonds” on the periodic table do not continue to produce the strongest “double bonds” or “triple bonds.” In fact, the opposite appears to be the case. This quantum chemical examination of nominal X = Y and X ≡ Y bonds in model molecules of atoms from the first three rows of the periodic table shows that the strongest “double bond” is in formaldehyde once the astrophysically-depleted Be and B atoms are removed from consideration. The strongest “triple bond” is a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Such behavior extends to aluminum-bearing molecules as well. For instance, recent studies have identified triplet ground states in small, aluminum-bearing molecules such as AlCH, AlOP, and AlNO. These small structures highlight that simple aluminum compounds appear to prefer to create triplet states instead of producing higher bond orders. The question of course, remains as to whether or not such behavior is standard in only small, Al-terminated molecules or if this is present in other Al-containing molecules. Only more data on such species can provide insights into this query.…”
Section: Introductionmentioning
confidence: 99%
“…Such behavior extends to aluminum-bearing molecules as well. For instance, recent studies have identified triplet ground states in small, aluminum-bearing molecules such as AlCH, AlOP, and AlNO. These small structures highlight that simple aluminum compounds appear to prefer to create triplet states instead of producing higher bond orders. The question of course, remains as to whether or not such behavior is standard in only small, Al-terminated molecules or if this is present in other Al-containing molecules. Only more data on such species can provide insights into this query.…”
Section: Introductionmentioning
confidence: 99%
“…The products of the reactions of alkali and alkaline-earth metals with small molecules, for instance, H 2 , CH 4 , and H 2 O, 1,2 have received special attention because of their importance in not only gas-phase reaction [3][4][5][6] and theoretical chemistries, [7][8][9] but also astrochemistry. [10][11][12][13][14] Among alkali and alkaline-earth metals, Mg is the most widely used and representative metal, and numerous Mg-bearing molecules, such as dual-ligand R 1 -Mg-R 2 and singleligand Mg-R 3 , in which R 1 , R 2 , and R 3 are generally non-metal atoms or groups, have been experimentally synthesized.…”
Section: Introductionmentioning
confidence: 99%